New genus and species of stripe-bellied rat Pseudoberylmys muongbangensis Tran. H. H., T. H. Viet, L. X. Canh, N. X. Dang, 2008 gen.sp.nov. (Mammalia, Rodentia, Muridae) from Vietnam - Hai, Tran Hong; Viet, Tran Hong; Canh, Le Xuan; Dang, Nguyen Xuan (Academia Journal of Biology, 2012)
After researching clearly about the appearance characteristics, form and microstructure of hairs, skull structure and form of 8 strange rat specimens and compare it with these other big rats of Vietnam, the authors has affirmed that this is a new genus and new species of rat and named that: New genus: Pseudoberylmys Tran. H. H, T. H. Viet, L. X. Canh, N. X. Dang, 2008 gen.nov. New species: Pseudoberylmys muongbangensis Tran. H. H, T. H. Viet, L. X. Canh, N. X. Dang, 2008 gen.sp.nov. Type material: Eight animals was collected during six years from 2002 to 2008. One Holotype with the number 2002-10-T3, 7 Paratype with the number 2003-02-T2, 2003-11-T5, 2004-04-T6, 2006-03-T2, 2007-10-T3, 2008-05-T4 and 2008-11-T7 are deposited in Vietnam Cryptozoic and Rare Animals Research Centre. Type locality: Soc village, Muong Bang commune, Phu Yen district, Son La province, Vietnam. Habitat: Pseudoberylmys muongbangensis Tran. H. H, T. H. Viet, L. X. Canh, N. X. Dang, 2008 gen.sp.nov. was found in the manioc field. Etymology: The new species was named after the commune Muong Bang, where the species was first found. Skull measurement: Occipitonasal length 51.8 - 56.4 Length of auditory bulla 8.0 - 8.7 Length of rostrum 17.8 - 20.5 Breadth of rostrum 12.8 - 14.7 Length of nasal 22.0 - 23.5 Zygomatic breadth 25.6 - 26.9 Length of bony palate 28.4 - 30.2 Interororbital breadth 7.5 - 8.0 Length of incisive foramina 10.5 - 11.2 Breath of braincase 19.5 - 21.2 Length of diastema 15.2 - 16.7 Zygomatic plate breadth 5.2 - 5.9 Leng of interparietal middle 6.5 - 7.5 Foramina insicive breadth 3.4 - 3.9 Length of toothrow maxilla 9.5 - 10.2 Breadth of greatest molar 2.6 - 2.8 Stripy-bellied rat’s skull have many points like with the Berylmys bowersi’skull: long and tapering rostrum, length of nasal bone is longer than 1/3 occipitonasal length, make up a triangular form which project to front and hide the incisors, reduce at rearward and fit in frontal bone to create an V shape. Frontal bone is strait, frontal and parietal joins is arched, parietal edge is short and don’t emerge, the lacrimal bone is very small. In profile of skull, the occiput is a incline plane which project to rearward. Below surface: Auditory bulla is big and bloat. The length of it is longer than 15% length of occipitonasal. Compare with the length of occpitonasal, length of bony palate is roughly 53.22% to 53.68%, length of diastema is roughly 28 to 19% and length of incisive foramina is roughly 19 to 20%. Description: The stripe-bellied rat belonging to the gray rat group in Vietnam. Its length of head and body is 220-260 mm, length of tail is 240-290 mm, length of hind feet is 50-55 mm, length of ears is 29-34 mm and mammals is 2-2 = 8. The pelage is coarse, but not spiny which have two kind of hair: 71-76% is soft underhairs, 24-29% is overhairs. In general, back is grizzled grayish-brown, made of many big overhairs beyond the overhairs which are gray at proximal and black at distal and overhairs is grayish white at proximal, blackish at medial and brownish yellow or dirty white at distal. Darker in the midline of back, paler on flanks to belly. The flanks is more speckled than back so flank’s color become more brownish than dorsal surface. Belly hairs (both overhairs and soft underhairs) are pure white, color of belly is sharply dimarcated from that of back. Specially that, the midline of belly skin from inguinal to breastbone is bare, flesh color with many across wrinkles which haven’t known its biological role. The midline wide is about 1/10 the belly wide. The colour of outside limbs is the same of flanks, inside color is the same of belly. Digits and dorsal surface of the hands and hind feet covered by white short hairs, but the midline dorsal surface of hind feet covered by blackish brown hairs. Tail is much longer than combined length of head and body, round in cross-section, bicolored (dark gray above, dirty white below) and near tip is whitish or pure white. Maxilla toothrow is long and medium size, The incisors are big, in profile is perpendicular with above nasal bone plane. Dental is strong, all of condyloit process, angular processes, coronoit processes develop very much. Differential diagnosis Based on these description and skull measurements, the new species - stripe-bellied rat can be distinguished from Berylmys bowersi, Leopoldamys edwardsi, L. sabanus, Bandicota indica and Dacnomys millardi.